2016
DOI: 10.1007/s11205-015-1225-x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Wealth and Mother’s Education in Infant and Child Mortality in 26 Sub-Saharan African Countries: Evidence from Pooled Demographic and Health Survey (DHS) Data 2003–2011 and African Development Indicators (ADI), 2012

Abstract: This study examined the regional differences in the role of wealth and mothers' educational attainment in explaining infant and child mortality in sub-Saharan Africa (SSA). Specifically, this study investigates the role of wealth and mothers' educational attainment in urban-rural and regional differences of SSA. We use data from Demographic and Health Surveys and the World Bank African Development Indicators to document these regional differences in infant and child mortality rates in SSA. Our findings show sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 27 publications
0
19
1
Order By: Relevance
“…They understand the importance of prenatal and neonatal care and its relation to mortality of infants and mothers. A recently published study in infant and child mortality rates in sub-Saharan Africa using the Demographic andHealth Surveys (2003-2011) and the World Bank African Development Indicators (2012) found that as a mother's education increases infant mortality decreases, regardless of whether the mother is living in an urban or rural region (Anyamele, Ukawuilulu, & Akanegbu, 2017). These data reinforce the importance of educating women to improve health outcomes.…”
Section: The Dividends Of Schooling In Africamentioning
confidence: 89%
“…They understand the importance of prenatal and neonatal care and its relation to mortality of infants and mothers. A recently published study in infant and child mortality rates in sub-Saharan Africa using the Demographic andHealth Surveys (2003-2011) and the World Bank African Development Indicators (2012) found that as a mother's education increases infant mortality decreases, regardless of whether the mother is living in an urban or rural region (Anyamele, Ukawuilulu, & Akanegbu, 2017). These data reinforce the importance of educating women to improve health outcomes.…”
Section: The Dividends Of Schooling In Africamentioning
confidence: 89%
“…Since DHS has a complex survey design, sampling weights are required to correct for the bias in probability selection [29]. Regression analysis was, therefore, done after adjusting for sampling design (stratification and clustering) using "svy" command in Stata/MP 15.1.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies use primary school completion and progression to secondary school and find lower mortality is associated with higher education levels (Gupta et al 2002;Gakidou et al 2010;Anyamele et al 2017).…”
Section: Educationmentioning
confidence: 99%